Unconventional lawmaking in the law of the sea - Klein, Natalie (Natalie S.) (Oxford : Oxford University Press, 2023)
'Unconventional Lawmaking in the Law of the Sea' explores the ways that actors operating at the international level are developing standards of behaviour to regulate varied maritime activities beyond traditional lawmaking. Other than conventions and customary international law, there is a plethora of international agreements that influence international conduct. This 'soft law' or 'informal law' is now prolific in ocean governance, and so it is timely to consider its significance for the law of the sea.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 2, 2023).
Keywords: Law of the sea; Maritime law; Soft law; Law; International law